2009
DOI: 10.1371/journal.pone.0006096
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Ortholog of Mammalian Translocator Protein (TSPO) with Virulence Regulating Activity

Abstract: The translocator protein (TSPO), previously designated as peripheral-type benzodiazepine receptor, is a protein mainly located in the outer mitochondrial membrane of eukaryotic cells. TSPO is implicated in major physiological functions and functionally associated with other proteins such as the voltage-dependent anionic channel, also designated as mitochondrial porin. Surprisingly, a TSPO-related protein was identified in the photosynthetic bacterium Rhodobacter sphaeroides but it was initially considered as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…This function for Tspo genes in erythropoiesis is supported by experimental evidence from avian and zebrafish models [9][10][11]. TSPO homologs have also been identified in plants and bacteria, where they have developed specialized functions [12,13]. In this review, we will summarize the evolutionary divergence of TSPO structure and its function(s).…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…This function for Tspo genes in erythropoiesis is supported by experimental evidence from avian and zebrafish models [9][10][11]. TSPO homologs have also been identified in plants and bacteria, where they have developed specialized functions [12,13]. In this review, we will summarize the evolutionary divergence of TSPO structure and its function(s).…”
Section: Introductionmentioning
confidence: 92%
“…In a recent study, the TSPO of the non-photosynthetic eubacterium Pseudomonas fluorescens was shown to share structural and functional characteristics with mammalian TSPO. The shared characteristics include binding for the high affinity diagnostic isoquinoline carboxamide ligand PK 11195, and involvement in bacterial adhesion and virulence [12]. Adhesion and expression of virulence factors are closely regulated by iron availability.…”
Section: Tspo In Bacteria and Archaeamentioning
confidence: 99%
See 3 more Smart Citations